2022
DOI: 10.36547/nbc.1023
|View full text |Cite
|
Sign up to set email alerts
|

Ag/SiO2 nanocomposite mediated by Escherichia coli D8 and their antimicrobial potential

Abstract: Silica (SiO2) has a fundamental role in the recuperation of plants in response to environmental stresses, besides the induction of resistance against plant diseases. Silver nanoparticles (AgNPs) have a superior antimicrobial activity. The combination between SiO2 and AgNPs is a promising approach due to their antimicrobial activity, biological activity, low toxicity, and high stability of the produced nanocomposite. The current study postulated a green method for silver/silica nanocomposite (Ag/SiO2NC) synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…). While B. subtilis ZBP4 biosynthesized ZnO NPs with irregular spherical shape and size range of 22-59 nm as reported by Hamk et al(2022). The current results confirmed the high stability of the biosynthesized ZnO NPs due to the high repulsion forces between the particles due to its high surface positive charge values which prevent their aggregation and agglomeration.…”
supporting
confidence: 87%
“…). While B. subtilis ZBP4 biosynthesized ZnO NPs with irregular spherical shape and size range of 22-59 nm as reported by Hamk et al(2022). The current results confirmed the high stability of the biosynthesized ZnO NPs due to the high repulsion forces between the particles due to its high surface positive charge values which prevent their aggregation and agglomeration.…”
supporting
confidence: 87%
“…Rodrigues et al ( 2020 ) demonstrated the biosynthesis of Ag/SiO 2 NC with AgNPs with a mean size of 45 ± 12 nm and a negative charge (− 35.5) using green tea extract. The positive charge of the nanomaterials increases the effective electrostatic association with the microbial cell wall's negative charges, allowing them to easily penetrate the cell membrane (El-Zahed et al 2022 ). FTIR and XRD results stated the purity of Ag/SiO 2 NC particles that formed exclusively from Si, oxygen and silver, which was in concurrence with Jeon et al ( 2003 ) and Wei et al ( 2014 ) results.…”
Section: Discussionmentioning
confidence: 99%
“…Ag/SiO 2 NC was prepared according to Sadeghi et al ( 2013 ) and modified by El-Zahed et al ( 2022 ). Briefly, AgNPs were biosynthesized in the presence of sunlight by mixing free-cell supernatant of E. coli D8 (filtered from overnight bacterial growth, inoculated by a 0.5 McFarland standard, 1–2 × 10 8 CFU/ml) with 1.5 mM of AgNO 3 solution (1:1 v/v).…”
Section: Methodsmentioning
confidence: 99%
“…A 0–10 mg/ml series from each compound was prepared, added separately into 0.5 MacFarland inoculated MHB and incubated at 37 °C or 28 °C for 24 hours or 7 days. After incubation, the microbial growth rates were measured spectrophotometrically at 600 nm [48] …”
Section: Methodsmentioning
confidence: 99%